A novel implementation of computational aerodynamic shape optimisation using Modified Cuckoo Search - Sean Walton (Applied Mathematical Modelling, 2016)
This paper outlines a new computational aerodynamic design optimisation algorithm using a novel method of parameterising a computational mesh using `control nodes'. The shape boundary movement as well as the mesh movement is coupled to the movement of user--defined control nodes via a Delaunay Graph Mapping technique. A Modified Cuckoo Search algorithm is employed for optimisation within the prescribed design space defined by the allowed range of control node displacement. A finite volume compressible Navier--Stokes solver is used for aerodynamic modelling to predict aerodynamic design `fitness'. The resulting coupled algorithm is applied to a range of test cases in two dimensions including aerofoil lift--drag ratio optimisation intake duct optimisation under subsonic, transonic and supersonic flow conditions. The discrete (mesh--based) optimisation approach presented is demonstrated to be effective in terms of its generalised applicability and intuitiveness.